Enhanced tensile properties and corrosion resistance of stainless steel with copper-coated graphene fillers - Li, Zhiqiang (2020)
Graphene (Gr) can significantly improve the mechanical properties of metal matrix materials. However, the reinforcing effect of Gr on stainless steel (SS) has rarely been investigated due to the difficulty in its uniform dispersion. In this study, 316L stainless steel was reinforced with copper-coated graphene (Gr-Cu/SS) through molecular level mixing, ball milling, and spark plasma sintering (SPS). The tensile strength and yield strength of Gr-Cu/SS have increased by 74.0% and 65.5%, respectively, with 0.2 wt% graphene added. The improvement on the tensile strength and yield strength of Gr-Cu/SS is attributed to the effective load transfer and the increase of relative density due to the addition of graphene. Moreover, the corrosion resistance of Gr-Cu/SS was improved, attributed to the low cathodic overvoltage of copper and the prevention of ionic transfer between stainless steel grains by graphene.